THE INFLUENCE OF HUMAN RESOURCES, COMMITMENT LEADER, THE USE OF INFORMATION TECHNOLOGY, AND SYSTEM INTERNAL CONTROL ON THE QUALITY OF LOCAL GOVERNMENT FINANCIAL REPORT PRINGSEWU - Chairul Anwar; Devi Meliana Mukadarul (International Conference On Law, Business and Governance (ICon-LBG), 2016)
This research aims is to know discover the effect of human resource, leader commitment, utilization of information technology, and internal control system on financial statements quality in Pringsewu’s Local Government. Respondents on this study were all employees of Pringsewu Local Goverment’s BPKAD. From 53 questionnaires handed off, 53 are valid to be processed later on. Analysis data used in this study is by SPSS 18.0 program. Statistic method used to do the hypothesis testing is multiple linear regression analysis. Hypothesis testing result shows these following outputs. First is, human resource has positive influence on financial statements quality significantly. The second, leader commitment has positive influence on financial statement quality significantly. Third is, utilization of information technology has positive influence on financial statement quality significantly. Last one is, internal control system has positive influence on financial statement quality significantly.